Industrial and organizational psychology : research and practice - Spector, Paul E. (John Wiley & Sons Singapore, 2012)
The text continues to focus on providing a clear, understandable, up-to-date text that covers the core material of the field while including the most cutting-edge topics, including technology, internationalization, skilled labour shortages, and occupational health psychology